First Identification of the New Severe Acute Respiratory Syndrome Coronavirus 2 Omicron Variant (B.1.1.529) in Italy. (21st January 2022) - Micheli, Valeria; Bracchitta, Fiorenza; Rizzo, Alberto; Mancon, Alessandro; Mileto, Davide; Lombardi, Alessandra; Stefanelli, Paola; Gismondo, Maria Rita
Abstract: We identified the first case in Italy of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) B.1.1.529 variant, using whole-genome sequencing in an Italian subject traveling from Mozambique. Specific mutation profiles deserve further investigations to clarify potential effects on vaccination efficacy. This case highlights the crucial role of rapid and continuous surveillance of SARS-CoV-2 variant circulation.